Application of microRNA Targeted 3′UTRs to Repress DHFR Selection Marker Expression for Development of Recombinant Antibody Expressing CHO Cell Pools. Issue 10 (16th July 2018) - Jossé, Lyne; Zhang, Lin; Smales, Christopher Mark
Abstract : The dihydrofolate reductase (DHFR) system is used for the selection of recombinant Chinese hamster ovary (CHO) cell lines using the inhibitor methotrexate (MTX). During clonal selection, endogenous DHFR expression, and resistance to MTX allows the selection of cells expressing sufficient DHFR to survive. Here, the authors describe a novel vector platform for the DHFR system, whereby addition of a synthetic 3′UTR destabilizes DHFR expression. miRs ability to negatively regulate gene expression by their near‐complementary binding to the 3′UTR region of transcripts are harnessed. From the literature, the authors identified let‐7f as a highly abundant, invariant miR in CHO cells. Three 3′UTR targets of the let‐7f miR are then cloned in the DHFR host 3′UTR to determine the impact on gene expression (HMGA2 3′UTR sequence 1, 2, and 3). Using luciferase as a reporter, the authors show down‐regulation of luciferase activity is mediated by the nature of the 3′UTR and its ability to bind let‐7f. The same 3′UTRs downstream of the DHFR gene to show this also results in reduced transcript amounts are then applied. Finally, the authors applied this methodology to generate stable DG44‐derived cell pools expressing a model monoclonal antibody (mAb), demonstrating this approach can be used for the selection of antibody‐producing cells with low MTX concentrations. Abstract : Let‐7 microRNAs are abundantly expressed in differentiated cells, including CHO models. The Let‐7 microRNA family reportedly inhibit the expression of LIN28, implicated in development, and expression of the oncogene HMGA2 . Here, the authors show that fragments of the HMGA2 3'UTR (1, 2, 3) can successfully repress luciferase reporter gene expression (top panel) and DHFR expression (bottom panel) models. The authors harnessed this to design a novel system with attenuated expression of the DHFR selection marker to increase stringency and improve recombinant protein yield from CHO cells.